Kemampuan Eceng Gondok (Eichhornia Crassipes) Sebagai Fitoremediasi Dalam Pengolahan Limbah Cair Industri Tempe - Putri, Wilda Nindia; Barus, Linda; Ahyanti, Mei; Prianto, Nawan; Masra, Ferizal; Indarwati, Suami (MIDWIFERY JOURNAL, 2023)
Background: This research is a Quasi-Experimental Design using a pretest-posttest with control group design with 3 repetitions. Objective: To determine the ability of 1 kg water hyacinth plants as phytoremediation in processing tempe liquid waste.Methods: This research is in the form of a Quasi-Experimental Design with the independent variables in the research, namely variations in wastewater volume of 20, 25, 30 liters and the dependent variable, namely reducing BOD, COD, TSS levels and neutralizing pH. This research was conducted at the Environmental Health Department Laboratory of the Tanjung Karang Health Polytechnic in March-May 2023. The sample used was tempeh liquid waste from a household industry located on Jalan Catur Tunggal, Kemiling District, Bandar Lampung.Results: From the research results, it was found that phytoremediation using water hyacinth plants weighing 1kg in a wastewater volume of 20 liters could reduce BOD levels by 57.13%, COD by 67.74%, TSS by 80.82%, and increase pH levels by 20.51%. . In accordance with Governor Regulation No. 7 Governor of 2010 concerning Waste Water Quality Standards for Soybean Processing Activities, only BOD with a waste water volume of 20 liters meets the requirements, other waste water volumes do not meet the standards.Conclusion and Recommendations: With the above results, phytoremediation using 1kg water hyacinth plants in a wastewater volume of 20 liters can reduce BOD levels by 57.13%, COD by 67.74%, TSS by 80.82%, and increase pH levels by 20.51%. A repeat study of similar phytoremediation is needed to get a better grade from this research. Keyword : Water Hyacinth Plants, Tempe Waste, BOD, COD, pH ABSTRAK Latar Belakang: Penelitian ini berupa Quasi-Experimental Design menggunakan rancangan pretest-posttest with control group dengan 3 kali pengulangan.Tujuan: Untuk mengetahui  kemampuan tanaman eceng gondok 1 kg sebagai fitoremediasi dalam pengolahan limbah cair tempe.Metode: Penelitian ini berupa Quasi-Experimental Design dengan Variabel bebas pada penelitian yaitu variasi volume air limbah 20, 25, 30 liter dan variabel terikat yaitu penurunan kadar BOD, COD, TSS dan menetralkan pH. Penelitian ini di lakukan di Laboratorium Jurusan Kesehatan Lingkungan Politeknik Kesehatan Tanjung Karang pada bulan Maret-Mei 2023. Sampel yang digunakan adalah limbah cair tempe dari industri rumah tangga yang berada di Jalan Catur Tunggal Kecamatan Kemiling Bandar Lampung.Hasil: Dari Hasil penelitian diperoleh hasil fitoremediasi menggunakan tanaman eceng gondok berat 1kg dalam volume air limbah 20 liter dapat menurunkan kadar BOD 57,13%, COD sebesar 67,74 %, TSS sebesar 80,82%, dan meningkatkan kadar pH sebesar 20,51%. Sesuai dengan Peraturan Gubernur Lampung No 7 Tahun 2010 Tentang Baku Mutu Air Limbah Kegiatan Pengolahan Kedelai yang memenuhi syarat hanya BOD dengan volume air limbah 20 liter, pada volume air limbah lainnya belum memenuhi standar.Kesimpulan dan Saran: Dengan hasil di atas fitoremediasi menggunakan tanaman eceng             gondok berat 1kg dalam volume air limbah 20 liter dapat menurunkan kadar BOD 57,13%, COD sebesar 67,74 %, TSS sebesar 80,82%, dan meningkatkan kadar pH sebesar 20,51%. Diperlukan kajian ulang tentang fitoremediasi serupa untuk mendapatkan grade yang lebih baik dari penelitian ini. Kata Kunci: Tanaman Eceng Gondok , Limbah Tempe, BOD, COD, pH